1995
DOI: 10.1159/000213728
|View full text |Cite
|
Sign up to set email alerts
|

Lipofuscin Accumulation and Ageing of Fibroblasts

Abstract: Lipofuscin accumulates in postmitotic cells. In human fibroblasts, accumulation of lipoftiscin as measured by cellular autofluorescence is exponential at first, but stops at a certain level. At the same time, cell death starts to decrease cell numbers significantly. Artificial lipofuscin-like material can be prepared by UV-crosslinking of mitochondria] preparations. This material is easily phagocytosed by human fibroblasts and results in an increased cellular lipofuscin accumulation. Such a forced lipofuscin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 10 publications
0
61
1
2
Order By: Relevance
“…A vicious circle involving ROS production might reinforce the mitochondrial defects and promote the accumulation of lipid and protein peroxidation products. 37 ROS accumulation can also result from and activate cellular stress pathways that participate in cell growth arrest. 23 Furthermore, ROS can trigger DNA damage, and a defective DNA repair response has been shown to be an important pathophysiological mechanism in premature ageing linked to genetically altered prelamin A maturation.…”
Section: Discussionmentioning
confidence: 99%
“…A vicious circle involving ROS production might reinforce the mitochondrial defects and promote the accumulation of lipid and protein peroxidation products. 37 ROS accumulation can also result from and activate cellular stress pathways that participate in cell growth arrest. 23 Furthermore, ROS can trigger DNA damage, and a defective DNA repair response has been shown to be an important pathophysiological mechanism in premature ageing linked to genetically altered prelamin A maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a telomerase transgene in cell lines derived from patients with Werner syndrome results in lengthened telomeres and replicative immortalization, thus indicating that the shortening of telomeres is a trigger of premature senescence in these cells (107). Several more recent reports showed that telomere shortening can be induced in fibroblasts by mild oxidative stress (533,602,603).…”
Section: E Oxidative Induction Of Telomere Shorteningmentioning
confidence: 99%
“…Cell injury by accumulation of lipofuscin arises due to the large amount of iron, which facilitates the generation of oxygen free radicals causing lysosome damage and destabilization of the cell by releasing free radicals or enzymes hidrolases 29 . It was suggested that this accumulation reduces the cellular protein turnover and the half-life of mitochondria causing degeneration and cell death 30 .…”
Section: Long Term Evaluation Of Morphometric and Ultrastructural Chamentioning
confidence: 99%